Entrepreneurs, investors and the state: the public and the private in sub-Saharan African irrigation development. Issue 11 (2nd November 2018) - Harrison, Elizabeth; Mdee, Anna
Abstract: This article draws on ethnographic research in Tanzania to interrogate the discourse of 'public' and 'private' in sub-Saharan irrigation development. It contrasts the complexity of social and political relations with narratives suggesting that 'private' is necessarily opposed and superior to 'public'. We argue that support for models of private-sector development obscures access to and control over resources and can result in the dispossession of those least able to resist this. Different interests of 'entrepreneurial' individuals and corporate investors and the ways in which these relate to the state are also glossed over. Conversely, the failure of the 'public' cannot simply be read from the chequered histories of irrigation schemes within which public and private interests intersect in complex ways.